Venture capital & the finance of innovation - Metrick, Andrew; Yasuda, Ayako (hoboken, NJ: Wiley, 2021)
"Many interesting developments have occurred in the world of venture capital since the publication of the first edition of this book in 2006, which prompted us to revise the book for the second edition. While the organization of the book remains unchanged, many of the chapters are substantially rewritten. For example, in Chapter 5, we re-ranked top VC firms, incorporating the latest performance statistics, fundraising and investment activities, notable exits, and (as always) our subjective opinions. In Chapter 6, we examine further evidence of the deepening globalization of the industry. In Chapters 3, 4, and 7,we analyze the impact of the 1999-2000 Internet bubble years on the VC risk and returns, as investments made in those years are finally mature and thus now a part of the performance evaluation analysis. We also incorporated expositional improvements throughout the book based on reader feedback on the first edition. Another feature of the new edition is that the VCV model, used extensively in Part III of the book, is now available as a Web-based application available on http://VCVtools.com. Significant collaborative efforts went into developing this tool, which we believe will be of interest to a broad audience, including practitioners interested in valuing VC-backed company stocks and employee stock options"--
Includes bibliographical references and index.
Keywords: Venture capital; Technological innovations -- Finance